Improved the electrochemical performance between ZnO@Li1.3Al0.3Ti1.7(PO4)3 solid electrolyte and lithium metal electrode for all-solid-state lithium-ion batteries. (20th January 2023) - Li, Jieqiong; Liu, Chengjin; He, Manyi; Nie, Shuqing; Miao, Chang; Sun, Shengwei; Xu, Guanli; Xiao, Wei
Highlights: The ZnO layer is introduced on the interface between LATP and Li. The layer can inhibit the growth of Li dendrites and improve structural stability. The Li/zno@LATP@zno/Li cell exhibits excellent cycle performance for 500 h. The licoo2 /zno@LATP/Li cell remains 118.5 mAh g −1 after 100 cycles at 0.1 c at 25 °C. Abstract: Spherical Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) solid electrolyte powders are first successfully synthesized by spray-drying and O2 pressure-controlled calcination processes, and then the targeted ZnO@LATP composite solid electrolytes are gained by coating 2 μm thickness of ZnO layer on the surface of the LATP powders, in which the ZnO layer effectively not only isolates the direct contact between LATP electrolyte sheet and lithium metal electrode, but also regulates the lithium deposition reaction on the surface of the electrolytes, thereby restraining the overgrowth of lithium dendrites to prolong the life span of the assembled coin cell. Specifically, the Li/ZnO@LATP@ZnO/Li symmetric cell enhances the cycle stability without obvious increment of the overpotential compared to the Li/LATP/Li cell at 0.4 mA cm −2 for 500 h, and the assembled LiCoO2 /ZnO@LATP/Li coin cell can deliver excellent rate and cycling performance, in which the discharge specific capacity is still retained at 118.5 mAh g −1 after 100 cycles at 0.1 C and quickly recovers to 121.2 mAh g −1 when the current is set back to 0.1 C after cycles. Furthermore, the ZnO@LATP solid electrolyte powders after being cycled present integrally spherical shape without any remarkable crack compared with the LATP solid electrolyte powders. Therefore, the investigations may provide an effective strategy to significantly lower the probability of side reactions between LATP electrolyte and lithium metal electrode to promote the electrochemical properties of LATP-based all-solid-state lithium-ion batteries. Graphical abstract: Schematic diagram of the structural stability and the cycling performance of the as-prepared solid electrolytes with and without the ZnO layer Image, graphical abstract